DEVELOPMENT OF HIGHER ORDER THINKING SKILLS (HOTS) QUESTIONS IN AKIDAH AKHLAK TO MEASURE CRITICAL THINKING SKILLS OF MADRASAH IBTIDAIYAH STUDENTS - Susilasari Susilasari; Mhmd Habibi; Rasyidi Rasyidi (Sekolah Tinggi Agama Islam Raudhatul Ulum, 2024)
This study addresses the lack of higher-order thinking Skills (HOTS)-based evaluation instruments in Akidah Akhlak learning that can measure the critical thinking abilities of Madrasah Ibtidaiyah (MI) students. The study aims to develop valid and reliable HOTS questions. The research employed the Tessmer development model, consisting of self-evaluation, expert validation, small group trials, and field testing. The subjects were fifth-grade students of MI Tarbiyah Islamiyah Mandah. Validation results from three experts showed an average validity score of 4.3, categorized as highly valid based on content, construct, and language aspects. Field testing revealed that most students fell into the “good” category for critical thinking skills, with an average score of 63.2%. This research produced ten sets of HOTS questions that meet validity and reliability criteria as evaluation instruments for Akidah Akhlak learning at the MI level. The findings contribute to developing HOTS-based learning instruments and recommend further research to create similar instruments for other subjects, expanding the population and integrating technology.